MIGRATION, REMITTANCES, AND LOCAL DEVELOPMENT IN MOLDOVA - Vitalie Ștîrba; Alexandru Stratan; Eugenia Lucașenco (Economy and Sociology)
Remittances and know-how transfer play a significant role in economic development in countries with high out-migration, and Moldova, in this regard, has been abundantly studied. In our research, we tried to assess the influence of remittances and knowledge transfer on local development from the point of view of migrants’ families, local entrepreneurs, and stakeholders. We used the empirical data obtained from a nationwide survey of about 600 rural households whose members experienced international migration and from the interviews with stakeholders and focus groups with farmers’ attendees. The results revealed that remittances often support the household's budget, covering the salary gap, and contribution on initiation of the local businesses. To encourage the investment of remittances in local infrastructure and entrepreneurship, the government launched several programs that aim to subsidize migrants’ business incentives. However, the results show that migrants prefer to invest in improving living conditions and are more reluctant to invest in their own businesses, either because of the lack of a market or because of institutional mistrust. The local authorities acknowledge the importance of remittances on local development, but at the same time, they are concerned about the demographic resilience of the localities and emphasize the lack of labor force caused by migration. In the context of labor shortage, entrepreneurs in the agricultural field admit that they have to improve the technology of production processes but also adapt their field of activity to one that requires less intensive manual work. The obtained results contribute to a better understanding of the influence of remittances on migrants’ households and local development.